Characterization of novel proteases identified by metagenomic analysis from dairy stabilization ponds - Irazoqui, Jose Matias; Eberhardt, María Florencia; Santiago, Gonzalo Manuel; Amadio, Ariel (Springer, 2024)
Cheese whey is the main by-product of dairy industries. It is used as a raw material for other value-added products, like whey protein concentrate. By using enzymes, this product can be further treated to obtain new higher value products, like whey protein hydrolysates. Proteases (EC: 3.4) represent a large segment of industrial enzymes, since they are used in several industries, including food. In this work, we describe three novel enzymes identified using a metagenomic approach. Metagenomic DNA from dairy industry stabilization ponds were sequenced, and the predicted genes were compared against the MEROPS database, focusing on families commercially used to produce whey protein hydrolysates. From a total of 849 candidates, 10 were selected for cloning and expression and three showed activities with both the chromogenic substrate, azocasein, and whey proteins. Particularly, Pr05, an enzyme from the yet uncultured phylum Patescibacteria, showed activity that is comparable to a commercial protease. All these novel enzymes could represent an alternative for dairy industries to produce value-added products from industrial by-products.